The AngioVac Device: Understanding the Failures on the Road to Success. Issue 6 (November 2016) - Worku, Berhane; Salemi, Arash; D'Ayala, Marcus D.; Tranbaugh, Robert F.; Girardi, Leonard N.; Gulkarov, Iosif M.
Abstract : Objective: Current percutaneous thromboembolectomy techniques may obviate surgical intervention in high-risk patients with iliocaval thrombus or thrombus of the right side of the heart, but typically require thrombus fragmentation and thrombolysis with associated bleeding and thromboembolic complications. The AngioVac (Angiodynamics, Latham, NY USA) device uses a percutaneous venovenous bypass circuit to aspirate intact thrombus. A review of the literature was performed with regard to the AngioVac device to determine the factors correlating with successful thrombus extraction. Methods: A literature search was performed with regard to use of the AngioVac device using the PubMed database. A meta-analysis was not performed given the small size and lack of statistical analysis of the individual reports included. Results: Twenty-three reports describing 57 procedures in 56 patients were analyzed. Indications for thrombectomy included iliocaval thrombus in 53% (30), thrombus of the right side of the heart, in 49% (28), pulmonary embolus in 14% (8), and upper extremity venous/Glenn shunt thrombosis in 7% (4). The complete success rate, defined as removal of all thrombus, was 75% (43), with an 11% (6) partial success rate. In 14% (8) of cases, minimal or no thrombus was retrieved. When analyzed by indication, iliocaval thrombus and thrombus of the right side of the heart demonstrated 87% (26) and 82% (23) complete success rates, respectively. Pulmonary embolus demonstrated a significantly lower success rate at 12.5% [1; ( P < .001)]. Complications occurred in 12% (7), including six hematomas and one retroperitoneal bleed. Conclusions: The AngioVac device offers an excellent alternative to surgical thrombectomy for patients presenting with iliocaval or intracardiac thrombus, with success rates of more than 80%, although it seems that pulmonary emboli are less amenable. Appropriate patient selection can lead to improved outcomes. Larger numbers are needed to make more definite conclusions.